EQUINE ASSISTED LEARNING: SYMBOLIC VALUE OF HORSE AS UNDERLYING PATTERN IN HUMAN THINKING - Gehtmane-Hofmane, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Traditional pedagogy do not stressed the unique and challenging needs of the adult learner for a different kind of educational experience that was more engaging, more flexible and more appreciative of the existing knowledge base and experience of the adult learning. Equine Assisted Learning is a practice in which adults engage in systematic and sustained self–educating activities in order to gain new forms of knowledge, skills, attitudes, or values. The purpose of this research is to illustrate the meaning and symbolic value of horse as underlying pattern in human thinking.